Effect of nurses' work environment on patient satisfaction: A cross‐sectional study of four hospitals in Japan. Issue 1 (29th June 2015) - Tei‐Tominaga, Maki; Sato, Fusako
Abstract: Aim: The Magnet Recognition Program is a system in the USA that recognizes a hospital as a magnet hospital for having a high retention rate of nurses and providing high quality patient care. The purpose of this study was to examine the effect of nurses' work environment with characteristics that are similar to those of magnet hospitals on patient satisfaction in Japan. Methods: The authors distributed anonymous self‐administered questionnaires in August 2011 to all nurses via the directors of the nursing departments of four private hospitals. The response rates were 91% ( n = 425) for nurses and 51% ( n = 379) for patients. In the questionnaire for nurses, the items addressed basic attributes and a scale of work environment characteristics of a magnet hospital (the Japanese version of the Practice Environment Scale of the Nursing Work Index [PES‐NWI]). The questionnaire for patients addressed basic attributes, information about their hospitalization, and items to assess patient satisfaction. To examine the effects of the PES‐NWI subscales on patient satisfaction, the authors conducted multivariate logistic regression analysis for groups, which were dichotomized by 75 percentile of the scores of patient satisfaction. Results: The result of model 1 in the multivariate logistic regression analysis demonstrated that collegial nurse–physician relations showed significant relationships with low patient satisfaction (odds ratio = 0.144, P < 0.05), while the significance was diminished in model 2, in which dummy variables of hospitals were entered into the equation. Conclusion: These findings suggested that a favorable work environment for nurses, which is similar to that of magnet hospitals, may influence patient satisfaction in hospitals in Japan.